The Effect Of Learning Media Management And Self-Motivation On Science Literacy Ability - Hidayati, Suci; Istiana, Lailatul; Karim, Abdul Malik (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2024)
The basis of this paper is the teacher's ability to manage the learning media used during learning because it is an important component in delivering teaching materials. Learning objectives can be effectively achieved if teachers can manage the media needs of each teaching material and use it appropriately. The post-pandemic learning process is felt to be less meaningful and tends to be boring for students, so teachers must be able to innovate in choosing and creating learning media that can motivate students to learn. This study aims to determine the benefits and effects of using "KARCIL" media in improving the science literacy of students of Madrasah Tsanawiyah. The focus of the paper lies in the use of "KARCIL" media in Natural Sciences (IPA) subjects with a quantitative approach of the field research model through interviews and observations and the distribution of questionnaires to students used as samples. The results of the study obtained were (1) There was a significant influence between the use of "KARCIL" media on science literacy skills students, amounting to 0.001 with a confidence level of 10%, (2) There was a significant influence between self-motivation and science literacy ability of 0.011 with a confidence level of 10% and (3) There is a significant influence between the value of the coefficient of determination for the Nagelkerke model of 64% and 36% influenced by other factors that are not studied. From the results of the study, it can be concluded that good management of learning media and appropriate use by teachers can improve students' literacy ability and learning achievement.